A new approach to corystospermales based on triassic permineralized stems from Argentina - Artabe, Analia Emilia Eva (2003)
Anatomically preserved mature stems of late Middle Triassic corystosperms from the Paramillo Formation of Argentina are described and assigned to Cuneumxylon spallettii gen. nov. et sp. nov. The silicified specimens show features of the pith, primary xylem and successive rings of secondary xylem and phloem. The most striking characteristic is the anomalous secondary growth, represented by secondary xylem bounded by arcs of secondary phloem probably derived from successive repositioned cambia. Cuneumxylon has two kinds of unusual centrifugal secondary growth. The first shows unequal activity of different portions of the cambium on the circumference of the axes; the consequent restriction of cambial activity to certain restricted areas develops wedged stems, which often split. The second produces polyxylic stems following supernumerary cambial activity. As in extant plants growing in arid regions, the included phloem and the associated parenchyma may have had functional value avoiding desiccation of the outer tissues of the stem during droughts. Anatomical features of other Corystospermaceae were used to determine systematic affinities and to establish relationships among medullosans, corystosperms and cycads.